Digital Сompetence of Russian School Teachers - Soldatova G.U; Shlyapnikov V.N (Moscow State University of Psychology and Education, 2015)
This article presents the results of digital competence study in different types of pedagogical stuff of Russian educational organization (informatics teachers - 140 participants, subject teachers - 145 participants, other categories - 112 participants) in comparison to the results of all-Russia digital competency study among schoolchildren and parents (2013). We use Index of Digital Competency to as¬sess the digital competence of schoolteachers. The results shows that schoolteachers significantly exceed schoolchildren and parents in digital competency (F(2)=32,03, p<0,001), in frequency of internet-usage ( χ2(14)= 597,61, p<0,001), in time spent in the Internet everyday ( χ2(14)=472,83, p<0,001). Also they prefer other types of devices for internet-activities. Informatics teachers significantly exceed other teachers in digital competency (F(2)=14,18, p<0,001). These results let make the conclusion that modern schoolteachers are able and ready to improve their pupils' digital competency by means of different ICT.